Empowerment of the Tofu Industry in Ponalan to Increase Sales through Digital Marketing - Naufal Afif; Prisca Nuraida; Rizki Arifiyanto; Arum Setiani; Dewi Wahyuningtias; Alkomah Fatmawati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The purpose of this service is to provide a new understanding and insight into the tofu industry with digitalized marketing and good branding. It will expand consumers from the products sold and retain existing consumers. The method used to achieve this goal is to carry out five stages of service activities: socialization, training, practice, mentoring, and evaluation. The results achieved are additional insights into the understanding and knowledge of AV Tahu Pong industry owners and employees operating social media as a means of digital marketing. In addition, this digitalized marketing is expected to have an economic impact on the AV Tahu Pong tofu industry.